2018
DOI: 10.20473/jn.v13i1.3478
|View full text |Cite
|
Sign up to set email alerts
|

Nurses Education and Motivation Towards Nursing Documentation

Abstract: Introduction: Nursing documentation is an integral part that cannot be separated from healthcare as a responsibility and accountability of nurses. High education and motivation are needed to achieve good nursing documentation. The aim of this study was to know the correlation between education and motivation of nurses towards Intensive Care nursing documentation.Methods: The design used was an analytical survey with a cross-sectional approach. The population was nurses in intensive care of Palembang BARI Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Similar results have been presented by other authors around the world (Gurková et al, 2013;Masum et al, 2016;Toode et al, 2015). A key challenge for every organization is to maintain the satisfaction of employees and increase their motivation (Ayalew et al, 2019), factors which may also affect the level of nursing record-keeping (Mediarti et al, 2018).…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…Similar results have been presented by other authors around the world (Gurková et al, 2013;Masum et al, 2016;Toode et al, 2015). A key challenge for every organization is to maintain the satisfaction of employees and increase their motivation (Ayalew et al, 2019), factors which may also affect the level of nursing record-keeping (Mediarti et al, 2018).…”
Section: Introductionsupporting
confidence: 86%
“…Although respondents working in the Internal Diseases Department have lower levels of amotivation, i.e., their motivation is higher (as is their job satisfaction), their level of nursing recordkeeping is significantly lower. In contrast, Mediarti et al (2018) found a connection between motivation and nursing documentation. Results such as ours potentially suggest that nurses in Croatia are overworked and do not perceive nursing recordkeeping to be in their scope of work.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…For example, nurses should be provided with education and training that presents the evidence about documentation and bias using specific examples of their own writing both when they are initially onboarded into a nursing position but also at regular intervals throughout their career as scholars suggest that nurses require ongoing support to maintain standards (Blair & Smith, 2012). Furthermore, researchers highlight that education has the most pressing affect on quality of documentation as defined by nursing staff (Kamil, Rachmah, & Wardani, 2018); specifically education improves motivation to document well (Mediarti, Rehana, & Abunyamin, 2018).…”
Section: Rele Van Ce To Clini C Al Pr Ac Ti Cementioning
confidence: 99%